Application of PI controller based active filter for harmonic mitigation of grid-connected PV-system - Achala Khandelwal; Pragya Nema (Bulletin of Electrical Engineering and Informatics, 2021)
The recent trends show the interconnection of PV system with electric grid. With this configuration the issue of harmonics comes into existence. The mounting figure of power-electronic instruments has formed considerable impression on the power-quality of electric supply. Harmonics deformations have conventionally been handled amid the application of passive-LC filters. Active Filter has emerged as a good substitute for passive filters to reduce the harmonics to great extent as it has numerous benefits over the former filters. The active filter’s most vital part is the applied control strategies. Several researches are being under process to advance the functioning of the filter. One of the important control requirements of filter is the regulation of DC link up capacitor voltage. Here the voltage supervision of capacitor is being done using PI controller. The paper show current harmonics compensation of PV grid connected system using PI controller based active filter. Simulation outcomes have been shown which displays the harmonics are within the IEEE boundaries.